2021
DOI: 10.1161/circresaha.121.319687
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage MST1/2 Disruption Impairs Post-Infarction Cardiac Repair via LTB4

Abstract: Rationale: Timely inhibition of inflammation and initiation of resolution are important to repair injured tissues. Mammalian STE20-like protein kinase 1/2 (MST1/2) acts as a regulator of macrophage-associated immune responses to bacterial infections. However, the role of MST1/2 in regulating macrophage phenotype and function in myocardial infarction (MI) remains unclear. Objective: To determine the function and underlying mechanism of macrophage MST1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 67 publications
2
22
0
Order By: Relevance
“…But another study indicated that upregulated P-STAT3 promotes anti-in ammatory M2 macrophage polarization and protects against AMI [48]. CXCL2, a neutrophil recruiting chemokine, elevated after AMI and involved in the process of in ammation-mediated myocardial injury [49][50][51]. DUSP is known as MAPK phosphatases (MKPs), which can dephosphorylate MAPKs.…”
Section: Discussionmentioning
confidence: 99%
“…But another study indicated that upregulated P-STAT3 promotes anti-in ammatory M2 macrophage polarization and protects against AMI [48]. CXCL2, a neutrophil recruiting chemokine, elevated after AMI and involved in the process of in ammation-mediated myocardial injury [49][50][51]. DUSP is known as MAPK phosphatases (MKPs), which can dephosphorylate MAPKs.…”
Section: Discussionmentioning
confidence: 99%
“…At a later stage on Days 3 to 7 after MI, anti-inflammatory macrophage subpopulations, which are associated with Arg1 (Arginase 1), are selectively recruited and may participate in the resolution of the postinfarction inflammatory response ( 111 ). The expression of YAP and TAZ was increased in macrophages undergoing proinflammatory or reparative phenotype changes ( 91 ), and the expression of endogenous MST1 in the cardiac macrophages of wild-type mice was decreased in the first 3 days after MI ( 92 ), suggesting the potential role of the Hippo pathway in the cardiac inflammatory response after MI. Genetic deletion of Yap / Taz in macrophages impairs the proinflammatory macrophage phenotype and promotes a reparative macrophage phenotype, which is accompanied by improved post-MI ventricular remodeling and heart function after MI.…”
Section: The Hippo-yap Pathway and Inflammation During Myocardial Inf...mentioning
confidence: 99%
“…In contrast, MP2 cells had high expression of anti-inflammatory genes such as Cd163 , Cbr2 , and Rgs10 . MP3 cells have mixed properties and express anti-inflammatory ( Slpi and Arg1 ) and proangiogenic ( Cxcl2 ) genes ( 92 ). Although no differences were observed in the numbers of infiltrated macrophages, monocytes, or neutrophils in Mst1/2 myeloid-specific knockout hearts compared to controls, there were differences in the numbers of the three macrophage subtypes, as indicated by increased MP1 cells and decreased MP2 and MP3 cells.…”
Section: The Hippo-yap Pathway and Inflammation During Myocardial Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…In macrophages, deficiency in Mst1/2 worsens cardiac dysfunction after myocardial infarction, as mice lacking Mst1/2 in their macrophages exhibited a marked increase in left ventricular end-diastolic and end-systolic volume and decrease in ejection fraction and fractional shortening ( Liu et al, 2021 ). In addition, the pharmacological inhibition of YAP/TAZ dampened pro-inflammatory gene expression (IL-1β and IL-12β) ( Mia et al, 2020 ).…”
Section: Mechanotransduction In Macrophages and Dendritic Cells Durin...mentioning
confidence: 99%